INSTRUSI AIR LAUT SUNGAI GANGSA - Salamun Salamun (KEAIRAN, 2008)
Estuary Phenomenon was construced by Tidal Range, Discharge and Sea Wave. Instrution was an impact of Fresh water and Sea Water or Salinity. Length of Instrution in Gangsa river can be forecasted by a model numerical which Saint Venant equation especially on continuity and momentum equation which was shown water surface and discharge. One of stop instrution on river is to build. Keywords : Gangsa River, Estuary Phenomenon ABSTRAK Fenomena Estuary terbentuk dari Pasang, Debit dan Gelombang Laut. Instruary adalah dampakdari menysupnya air laut/salinitas kerah air tawar/sungai. Panjang instrusi Sungai Gangsa dapat diramalkam dengan Numerik dengan persamaan Saint Venant khususnya pada Continuitas dan momentum yang ditunjukkan oleh elevasi muka air dan debit. Peramalan ini adalah salah satu cara penentuan bangaunan penanggulangan instrusi air laut. Kata kunci : Debit Sungai, Pasang Surut dan Salinitas.